2022
DOI: 10.1111/ipd.12938
|View full text |Cite
|
Sign up to set email alerts
|

At what age do children have the motor development to adequately brush their teeth?

Abstract: Background There is no consensus regarding when children are ready to brush independently. Aim To examine the effects of chronological age and motor development on toothbrushing effectiveness in 5‐ to 7‐year‐old children. Design In this cross‐sectional study, the change in Oral Hygiene Index (OHI) score and the improvement in OHI category (eg, poor to fair) were used to measure toothbrushing effectiveness. Motor development was assessed using the Beery‐Buktenica Developmental Test of Visual Motor Integration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
2
4
0
1
Order By: Relevance
“…Since the motor skills of most pre-school-aged children are not sufficient for effective brushing, it is recommended that they brush their teeth under the supervision of parents. 19 In previous studies, similar to our study, dental neglect is associated with poor oral health. 2,3 However, frequent snacking was found to be associated with dental neglect in children in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since the motor skills of most pre-school-aged children are not sufficient for effective brushing, it is recommended that they brush their teeth under the supervision of parents. 19 In previous studies, similar to our study, dental neglect is associated with poor oral health. 2,3 However, frequent snacking was found to be associated with dental neglect in children in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, it was found that the children mostly brushed their teeth once a day and on their own, and the presence of high plaque was found. Since the motor skills of most pre‐school‐aged children are not sufficient for effective brushing, it is recommended that they brush their teeth under the supervision of parents 19 . In previous studies, similar to our study, dental neglect is associated with poor oral health 2,3 .…”
Section: Discussionsupporting
confidence: 80%
“…According to National Health Service (NHS) guidelines, parents should supervise brushing until at least the age of seven [ 19 ]. A possible explanation for this is that elementary school children (≥ 6 years old) have adequate motor skills to brush their teeth independently [ 20 ]. In the present study, more than half of the participants (57.64%) believed that parents should supervise brushing until the child can do it independently regardless of their chronological age.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the Primary 4 class pupils is for the following reasons: the pupils' ages range from seven to nine years, and they usually would have started supervised but unassisted oral hygiene practices like tooth brushing. [20,21] The age group (7-9 years) also has a higher likelihood of providing better responses during the interviews than younger people from the lower classes. [22] Moreover, pupils in the Pry 4 class are more likely to remain in their various schools through the proposed study period, unlike those in higher classes (Pry 5 and Pry 6) who may be nursing the idea of writing the secondary school qualifying examinations (common entrance examinations) and leaving their various schools while this study is still ongoing.…”
Section: Study Populationmentioning
confidence: 99%